Media Internalized Pressure and Restrained Eating Behavior in College Students: The Multiple Mediating Effects of Body Esteem and Social Physique Anxiety - Fu, Tiantian; Wang, Jun; Xu, Shanshan; Yu, Jinrong; Sun, Guoxiao (Frontiers in Psychology, 2022)
Background: People’s lives have been greatly affected by the pandemic of the Novel Coronavirus (COVID-19). Considering the prevalence of college students’ restrained eating behavior and the harm it causes, it is essential to explore the associated factors. The aim of this study was to explore the association among media internalized pressure, body esteem, social physique anxiety, and restrained eating behavior. Methods: Participants in this study were 1032 Chinese college students (439 males and 593 females). They completed the Sociocultural Attitudes Toward Appearance Questionnaire-3, Body Esteem Scale, Social Physique Anxiety Scale, and Dutch Eating Behavior Questionnaire. Results: The results showed that media internalized pressure was significantly and positively associated with college students’ restrained eating behavior, that body esteem and social physique anxiety played a mediating role between media internalized pressure and restrained eating behavior, respectively, and that body esteem and social physique anxiety can also play a chained mediating role. Conclusion: This study reveals the impact of media internalized pressure on restrained eating behavior and, more importantly, the important role played by body esteem and social physique anxiety. It helps to reduce the occurrence of restrained eating behavior among college students.